Analysis of cash flow statement - Brycz, Bogumiła; Pauka, Marek (Analiza rachunku przepływów pieniężnych, 2012)
In the literature there is often emphasized the importance of cash flow analysis as an integral part of financial analysis, however the traditional cash flow analysis is limited to the vertical analysis of net cash flow from three levels of activities and, more rarely, to ratio analysis based on these three net cash flows. The purpose of the article is to evaluate the usefulness of such an analysis in the assessment of a company’s financial position with the aim of improving it. Therefore, based on the literature review on the cash flow analysis, the authors highlight the usefulness of the decomposition analysis of the cash flow statement and propose a procedure for conducting such an analysis, in particular they propose making an in-depth analysis of the cash flow from operations consisting of several stages
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 131-140
Keywords: cash flow statement; financial analysis; cash flow analysis; rachunek przepływów pieniężnych; analiza finansowa; analiza przepływów pieniężnych